Factors affecting Teaching and Learning of Religious and Moral Education (RME) in Junior High Schools Ghana: A Case Study Of C.B. Mensah Sda Junior High School - Collins Boafo; Adam Konadu; Charles Kofi Twene (Noyam Journals, 2024)
Religious and Moral Education (RME) has caught the attention and interest of Ghanaians from the past to our contemporary times. The subject seeks to enforce knowledge and values capable of making individuals responsible and resourceful members of society. In current times characterized by moral decadence, the need for religious and moral education has become a necessity. To realize the communal hope of making RME a lucrative and highly patronized course or subject in the education system in Ghana, it is necessary to look at the factors that affect the teaching and learning of RME in the country. This paper therefore sought to find out the significant factors that affect the teaching and learning of RME and the means to address such issues. A mixed approach was adopted in gathering the data from the C. B. Mensah Adventist Junior High School in the Ashanti Region of Ghana. The study revealed that the RME curriculum is facing some difficulties in Ghana. These include scarcity of textbooks and shortage of professional teachers in the subject area. The study recommended that the government, and other stakeholders involved in or patronizing education, should collaborate in addressing the challenges and implement sustainable measures for enhancing the teaching and learning of RME in Ghana. The study is relevant for teachers and learners alike because it contributes to knowledge development by serving as secondary material for future research and policymaking. It also serves as insight for the government, parents, teachers, religious bodies, educationists, counselors and other stakeholders in the educational sector.